2022
DOI: 10.3390/ijerph19074145
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Factors Contributing to the Smoking Behaviour among Hong Kong Chinese Young Smokers during COVID-19 Pandemic: A Qualitative Study

Abstract: COVID-19 has significant impacts on young smokers in their smoking behaviors. This qualitative study summarises the lived experience of young smokers during COVID-19. Moreover, through their lived experience, we aim to understand how the COVID-19 pandemic influence tobacco use behaviours in this population. A purposive sampling of 48 smokers aged between 17–25 years old is individually interviewed for 30 to 45 min. All interviews are transcribed in verbatim and analysed by two researchers separately using Cola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
2
5
0
Order By: Relevance
“…We successfully achieved data saturation after recruiting and interviewing 44 respondents who were self-reported to exhibit solitary drinking behaviour. The current sample size was comparable to other descriptive phenomenological studies on addictive behaviours [ 23 , 24 , 25 ]. Of the respondents, 72.7% (n = 32) participated the interviews face-to-face, and the remaining opted to participate via online.…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…We successfully achieved data saturation after recruiting and interviewing 44 respondents who were self-reported to exhibit solitary drinking behaviour. The current sample size was comparable to other descriptive phenomenological studies on addictive behaviours [ 23 , 24 , 25 ]. Of the respondents, 72.7% (n = 32) participated the interviews face-to-face, and the remaining opted to participate via online.…”
Section: Resultssupporting
confidence: 71%
“…We suggest that future studies examine the role of the identified factors in this qualitative study, including enhancement and coping drinking motives, social discomfort, reduced self-control, automatic mental processes, and desperate reactions to stressors using a quantitative approach, and determine how these factors relate to solitary drinking among adolescents and young adults by controlling the confounders, such as socioeconomic factors via different statistical methods, such as linear or logistic regression. This sequential approach is also commonly adopted in the field of addictive behaviours [ 23 , 24 , 25 , 52 , 53 ]. Fifth, age would influence our respondents’ responses in the semi-structured interviews.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to the interviews, the researcher (QL) did not have any relationship established with the participants and their parents. This is a common practice in qualitative studies in this population group [ 31 , 32 , 33 , 34 ]. In addition, all participants and their parents were told that QL was a PhD student from a University in Hong Kong.…”
Section: Methodsmentioning
confidence: 99%
“…The study interviewed adolescents from Hong Kong who smoked, purposively selecting equal numbers of those who had increased, decreased, or had not changed their smoking. The authors found that tobacco use behaviors patterns decreased as a result of spending more time at home, having fewer social gatherings, concern over finances, and decreases in access, while family tensions and lack of social interaction led to increases in smoking for others ( Lam et al, 2022 ). The authors also found that participants were aware that smoking could increase risks of COVID.…”
Section: Introductionmentioning
confidence: 99%